Pharmacogenomic Next-Generation DNA Sequencing: Lessons from the Identification and Functional Characterization of Variants of Unknown Significance in CYP2C9 and CYP2C19 - Devarajan, Sandhya; Moon, Irene; Ho, Ming-Fen; Larson, Nicholas B; Neavin, Drew R; Moyer, Ann M; Black, John L; Bielinski, Suzette J; Scherer, Steven E; Wang, Liewei; Weinshilboum, Richard M; Reid, Joel M (Drug metabolism and disposition, 2019)
and are highly polymorphic pharmacogenes; however, clinically actionable genetic variability in drug metabolism due to these genes has been limited to a few common alleles. The identification and functional characterization of less-common open reading frame sequence variation might help to individualize therapy with drugs that are substrates for the enzymes encoded by these genes. The present study identified seven uncharacterized variants each in and using next-generation sequence data for 1013 subjects, and functionally characterized the encoded proteins. Constructs were created and transiently expressed in COS-1 cells for the assay of protein concentration and enzyme activities using fluorometric substrates and liquid chromatography- tandem mass spectrometry with tolbutamide ( ) and (S)-mephenytoin ( ) as prototypic substrates. The results were compared with the SIFT, Polyphen, and Provean functional prediction software programs. Cytochrome P450 oxidoreductase (CPR) activities were also determined. Positive correlations were observed between protein content and fluorometric enzyme activity for variants of ( < 0.05) and ( < 0.0005). However, 709G>C and 65A>G activities were much lower than predicted based on protein content. Substrate intrinsic clearance values for 218C>T, 343A>C, and 337G>A, 518C>T, 556C>T, and 557G>A were less than 25% of wild-type allozymes. CPR activity levels were similar for all variants. In summary, sequencing of and in 1013 subjects identified low-frequency variants that had not previously been functionally characterized. In silico predictions were not always consistent with functional assay results. These observations emphasize the need for high-throughput methods for pharmacogene variant mutagenesis and functional characterization.